Insomnia disorder: when sleep plays coy, aloof and disdainful - K. Outhoff (South African Family Practice)
Intermittent or acute insomnia is common and may sometimes require short term treatment with approved hypnotic agents. A diagnosis of insomnia disorder, however, indicates that poor night-time sleep is chronic and is accompanied by significant impairment of daytime functioning. Although insomnia disorder often co-exists with psychiatric and medical conditions, it is viewed as an independent entity with potentially serious sequelae, requiring its own treatment, usually in the form of cognitive behavioural therapy (CBT), with or without pharmacotherapy.